On the operationalisation of values, flexibility and sustainability in curricula adhering to MQF 2.0 2024 - Gunawan, Teddy Surya; Kartiwi, Mira (Universiti Malaysia Perlis, 2026)
The Malaysian Qualifications Framework (MQF) 2.0 Addendum 2024 emphasises Values-Based Education (VBE), Flexible Learning Pathways (FLP), the Global Sustainability Agenda (GSA), and harmonisation with sectoral frameworks to strengthen graduate readiness and institutional compliance. As the 2026 compliance audit approaches, programme owners at undergraduate and postgraduate levels require a systematic approach to integrate these emphases into curricula. This paper analyses the evolution of the MQF, comparing MQF 1.0, MQF 2.0 (2017), and MQF 2.0 Addendum (2024), while contextualising global frameworks such as UNESCO's Education for Sustainable Development, the ASEAN Qualifications Reference Framework, and the Washington Accord. We propose a structured operationalisation framework aligning Programme Learning Outcomes (PLOs), Course Learning Outcomes (CLOs), and curriculum delivery with MQF's four emphases, while embedding SDG targets and IR4.0 competencies within teaching, learning, and assessment strategies. The framework is designed to be adaptable across disciplines, enabling institutions to implement policy-driven curriculum transformation regardless of programme type. Challenges in values assessment, curriculum flexibility, and staff readiness are discussed, alongside strategies for audit documentation and stakeholder engagement. This paper presents a practical and scalable model to guide Malaysian higher education institutions in aligning their curricula with MQF 2.0 Addendum 2024, ensuring audit-readiness and supporting the development of holistic, industry-ready graduates aligned with national and global policy aspirations